2007
DOI: 10.1530/rep-06-0083
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the expression of gallinacins, antimicrobial peptides, in ovarian follicles during follicular growth and in response to lipopolysaccharide in laying hens (Gallus domesticus)

Abstract: The aim of this study was to identify the types of gallinacin genes (GALs) expressed in ovarian follicles and to determine the changes in their expression during follicular growth and in response to lipopolysaccharide (LPS). Follicles at different stages of growth were collected from laying hens (nZ5) and LPS-injected hens (nZ3). The expression of GALs in the theca and granulosa layers was examined by semi-quantitative RT-PCR. The expression of GAL-1, -2, -7, -8, -10, and -12 in the theca layer and GAL-1, -8, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 26 publications
1
21
0
1
Order By: Relevance
“…TLRs also mediate induction of antimicrobial peptides [19]. Expression of gallinacins (GALs), a class of antimicrobial peptide of chicken, in the theca layer is enhanced by LPS [23]. In mammals, expression of antimicrobial peptide β-defensin-2 is regulated by TLR-4 in response to LPS in intestinal epithelial cells [44].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…TLRs also mediate induction of antimicrobial peptides [19]. Expression of gallinacins (GALs), a class of antimicrobial peptide of chicken, in the theca layer is enhanced by LPS [23]. In mammals, expression of antimicrobial peptide β-defensin-2 is regulated by TLR-4 in response to LPS in intestinal epithelial cells [44].…”
Section: Discussionmentioning
confidence: 99%
“…This dose was sufficient to induce an immune response in our previous study [23]. The stock solution of LPS was prepared by dissolving LPS from E. coli 0111:B4 (Wako Pure Chemical, Osaka, Japan) in Dulbecco's phosphate buffer (Nissui Pharmaceutical, Tokyo, Japan) at 4 mg/ml concentration.…”
Section: Tissue Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yoshimura et al (35) reported that inoculation of cell cultures of the hen oviduct with Salmonella enterica serovar Enteritidis and lipopolysaccharide (LPS) increased the expression levels of AvBD1, AvBD2, and AvBD3. Upregulation of AvBD1, AvBD7, and AvBD12 in the theca layer of ovarian follicles in LPS-injected laying hens has also been demonstrated (24). AvBD4 was expressed significantly in the liver of chickens in response to Salmonella serovar Enteritidis and serovar Typhimurium (17).…”
mentioning
confidence: 86%
“…The sequencing of the chicken (Gallus gallus) genome revealed the presence of a cluster of 14 different genes on chromosome 3 coding for avian defensins and designated as AvBD1 to -14 (22), with specific tissue distribution (13,(22)(23)(24)(25). Proteomic analyses of the chicken egg revealed the presence of AvBDs, especially AvBD9, AvBD10, and AvBD11, identified in the egg yolk, eggshell, and eggshell/egg white/vitelline membrane, respectively (26 -29).…”
mentioning
confidence: 99%